Molecular Characterization of Anguilla sp. with Special Notes on Its Population Genetic in the Rivers of Cilacap Central Java, Indonesia - Agus Nuryanto; Sri Riani; Dian Bhagawati; Elly Tuti Winarni; Farida Nur Rachmawati (Biosaintifika: Journal of Biology & Biology Education, 2022)
Taxonomic status of Anguilla species in the rivers of Cilacap is vital for further study, such as population genetics and evolutionary history. Taxonomic status, population genetic, and evolutionary histories of Anguilla can be assessed using single genetic marker, such as cytochrome oxidase 1 gene. This study aimed to determine taxonomic status, genetic diversity and connectivity, and evolutionary history of Anguilla populations in the rivers of Cilacap. Anguilla samples were collected from Doplang-Serayu and Segara Anakan watersheds.  Sequence homology test to the conspecific sequence in GenBank proved that all samples from Doplang-Serayu watershed were genetically identified as Anguilla bicolor (98.23 to 100% homology). The decision was supported by monophyly between samples and their conspecific references. Anguilla bicolor from both watersheds had high haplotype (gene) diversity. Amova and Fst analysis proved that no genetic difference (p=0.623) was observed between Doplang-Serayu and Segara Anakan watersheds, indicated panmixing.  Haplotype network proved that both populations were evolved from two primitive ancestors. This study concluded that Anguilla bicolor was the only freshwater eel observed in the rivers of Cilacap. Anguilla bicolor in the rivers of Cilacap has high genetic diversity but no genetic differentiation was observed among populations. Anguilla bicolor population in the rivers of Cilacap evolved from two primitive ancestors.